62.0k views
1 vote
Please show steps to get answer: thanks 2(8p-2) = 5p-15

1 Answer

0 votes

In order to solve this equation for p, first we need to use the distributive property of multiplication in the product with brackets on the left side of the equation:


\begin{gathered} a(b+c)=ab+ac \\ 2(8p-2)=2\cdot8p-2\cdot2=16p-4 \end{gathered}

Then, we can do the following steps:


\begin{gathered} 16p-4=5p-15 \\ \to\text{put the like terms on the same side of the equation:} \\ 16p-5p=-15+4 \\ \to\text{add the like terms:} \\ 11p=-11 \\ \to\text{divide both sides by the coefficient of p:} \\ (11p)/(11)=(-11)/(11) \\ p=-1 \end{gathered}

Therefore the solution is p = -1.

User Sumit Munot
by
6.4k points